Arsenic contamination in surface and groundwater in major parts of Manikganj district, Bangladesh - Akter, Atia; Mia, MY; Zakir, HM (Journal of the Bangladesh Agricultural University, 2016)
The contamination of groundwater by arsenic (As) in Bangladesh is the largest poisoning of population in history, with millions of people exposed. Thirty (30) water samples were collected from 5 different Upazilas of Manikganj district in Bangladesh to determine the concentration of As as well as to assess the level of contamination. Concentrations of As in waters were within the range of 0.27 to 1.96; 0.43 to 5.09; trace to 6.69 mg L-1 at Singair, Harirampur and Ghior Upazila, respectively. But the concentration of As in waters both of Manikganj sadar and Shivalaya Upazila were trace. All surface and groundwater samples of Singair and Harirampur, and 4 groundwater samples of Ghior Upazilas exceeded Bangladesh standard value for As concentration (0.05 mgL-1). The highest As concentration (6.69 mgL-1) was found in groundwater of Baliakhora village of Ghior upazila in Manikganj district. The cation chemistry indicated that among 30 water samples, 15 showed dominance sequence as Mg2+ > Ca2+ > Na+ > K+ and 14 samples as Ca2+ > Mg2+ > Na+ > K+. On the other hand, the dominant anion in water samples was Cl- followed by HCO3- and SO42-. Highly significant positive correlations were found in between the concentrations of As and SO42-(r=712**),and As and Ca2+ (r=581*), suggesting similar sources and/or similar geochemical processes controlling the occurrence of these ions in waters. J. Bangladesh Agril. Univ. 13(1): 47-54, June 2015